The Relationship Between Emotional Expression and Marital Satisfaction Among Couples Living with Parents or In-Laws - Putri, Arum Erlita; Kusumaningrum, Fitri Ayu (Unisia, 2024)
Marriage remains a critical institution influencing individual well-being, family stability, and social cohesion, particularly in collectivist contexts where multigenerational households are common. This study aimed to examine how emotional expressivity—both positive and negative—relates to marital satisfaction among Indonesian couples living with parents or in-laws. Using a quantitative, cross-sectional, correlational design, data were collected from 67 married individuals through validated Indonesian adaptations of the ENRICH Marital Satisfaction scale and the Self-Expressiveness in the Family Questionnaire. Descriptive analyses indicated generally low levels of marital satisfaction, medium to high positive expressivity, and low negative expressivity. Correlation results revealed that positive expressivity was significantly associated with higher marital satisfaction, whereas negative expressivity predicted lower satisfaction, though with varying strength across subgroups. Demographic analyses showed that gender, marital duration, number of children, and income moderated these associations, with positive expressivity particularly salient for women, couples in mid-marriage, and those at or below the minimum wage. These findings align with prior research emphasizing the protective role of positive emotional communication and the risks of negative expression, while extending these insights into the Indonesian cultural context. The study contributes theoretically by integrating cultural and structural moderators into models of marital satisfaction and practically by suggesting that marital counseling and policy initiatives should promote constructive emotional expression to sustain marital stability. Overall, the findings underscore that in multigenerational households, emotional expressivity functions as a key determinant of marital well-being and resilience.